Adapted approaches to initial fluid management of patients with major burns in resource-limited settings: A systematic review - Kai Hsun Hsiao; Joseph Kalanzi; Stuart B Watson; Srinivas Murthy; Ani Movsisyan; Kavita Kothari; Flavio Salio; Pryanka Relan (Burns Open)
Background: Resource limitations in settings such as burn mass casualty incidents (MCIs) present challenges to the judicious fluid resuscitation required for major burns. Previous recommendations for burns care in MCIs have suggested certain adaptations from routine care, such as delaying intravenous (IV) fluid resuscitation until arrival at facility; using a fluid calculation formula that is independent of percentage of total body surface area (%TBSA) burned; or using fluid calculation formula based on time of arrival to first receiving facility rather than from time of injury, thus omitting ‘catch-up’ fluid. Objectives: To synthesize and assess certainty of evidence from resource-limited settings on the three adaptations to fluid resuscitation for patients with major burns in MCIs. Methods: PubMed, EMBASE, CINAHL, and Cochrane Library were searched on 8 September 2023 with an update search on 8 July 2024. Primary quantitative studies in resource-limited settings meeting eligibility criteria as assessed by two reviewers were included. Where available, outcome effects for these adaptations compared to routine burns care were calculated. Evidence certainty was determined by GRADE. Results: Two eligible studies were identified from 544 search results. One study with 48 participants provided very uncertain evidence that delayed IV fluid resuscitation may increase acute kidney injury compared to prehospital resuscitation (OR 2.48, 95% CI 0.58–10.62). The other study with a cohort of 10 children provided very uncertain evidence that calculating fluid requirements based on time of arrival to first receiving facility, i.e. omitting ‘catch-up’ fluids, may maintain adequate urine output and be associated with no complications of fluid over- or under-resuscitation. There were no studies on use of a simplified %TBSA-independent fluid calculation formula. Conclusions: There is very limited and uncertain evidence to inform on delayed IV fluid resuscitation, simplified %TBSA-independent formula, and omission of ‘catch up’ fluids for burns care in MCIs. Contextual factors, local values, preferences and feasibility also need to be considered.